Computerized Preliminary Screening of Children With Learning Disabilities - Brosseau, John F.; Fox, Janette M.; Romaniuk, Eugene (Canadian Journal of Counselling and Psychotherapy, 2012)
A computerized program was developed to screen students with learning disabilities, using standardized tests from student records. The selection method utilizes the Tinker-Bond Formula: (# years in school) x (I.Q. Score)/100 + 1 = reading expectancy. The expected reading level is compared to the child's actual reading level on standardized test. Children who are one-third or more behind their expected reading level would be identified as having a possible learning disability.